Kinerja Usaha Mikro Kecil Dan Menengah (UMKM) Ditinjau Dari Perspektif Balance Scorecard (BSC) - I Wayan Rudiana; Ni Putu Ayu Kusumawati; Ni Wayan Alit Erlina Wati (Hita Akuntansi dan Keuangan, 2022)
The Balanced Scorecard is an approach to assessing company performance because it canprovide a comparison of the financial and non-financial sides. The method used in thisresearch is descriptive quantitative method. Perspective The results in this study indicatethat the financial perspective, ROE, DER, and CR obtain good criteria. The customerperspective gets good criteria and the results of the satisfaction questionnaire are verysatisfying to the company's performance. The internal business received the results ofinnovation and operations carried out by the company went well. The perspective oflearning and growing obtains satisfactory results. Final assessment, all criteria in thecategory are quite good.